Comparative analysis of microbial communities in different growth stages of Dermacentor nuttalli - Zhao, Li; Ma, Yi-Min; Yang, Bo; Han, Wen-Xiong; Zhao, Wei-Hong; Chai, Hai-Liang; Zhang, Zhan-Sheng; Zhan, Yong-Jie; Wang, Li-Feng; Xing, Yu; Yu, Lu-Fei; Wang, Jin-Ling; et al. (Frontiers in Veterinary Science, 2022)
Ticks were the first arthropods to be identified as pathogen vectors. Dermacentor nuttalli is the dominant tick species in Inner Mongolia, and it carries and transmits a wide range of pathogenic microorganisms. However, at present, tests are only available for adult D. nuttalli ticks and different developmental stages of D. nuttalli carrying one specific pathogen, as well as next-generation sequencing of adult D. nuttalli ticks. In this study, we investigated the microbial community structures of D. nuttalli in different growth stages under laboratory artificial feeding conditions. Total DNA was extracted from seven growth stages (female adult ticks, eggs, larval ticks, engorged larval ticks, nymphal ticks, engorged nymphal ticks, and second-generation adult ticks) obtained from laboratory artificial feeding of D. nuttalli female ticks in Inner Mongolia. Then, the 16S rDNA V3–V4 hypervariable region was amplified to construct an Illumina PE250 library. Finally, 16S rRNA sequencing was performed on Illumina Novaseq 6000 platform. The sequencing data were analyzed using molecular biology software and platforms. The Illumina PE250 sequencing results showed that the egg stage had the highest diversity and number of species, while the engorged nymph stage had the lowest diversity and number of species. A total of 387 genera of 22 phyla were annotated in D. nuttalli, with 9 phyla and 57 genera found throughout all 7 growth stages. The dominant phylum was Proteobacteria; the dominant genera were Arsenophonus and Rickettsia; and the genera with the highest relative abundance in the 7 growth stages were Pseudomonas, Paenalcaligenes, Arsenophonus, Arsenophonus, Pseudomonas, Arsenophonus, and Rickettsia, respectively. Among the 23 exact species annotated, Brucella melitensis exhibits pathogeny that poses a serious threat to humans and animals. In this study, the microbial community composition at different growth stages of D. nuttalli was comprehensively analyzed for the first time.